ANAEROBIC-AEROBIC TREATMENT OF TEXTILE WASTEWATER IN A SEQUENCING BATCH REACTOR - IBTISSAM KANBOUCHI; SALAH SOUABI; ABDESSADEK CHTAINI; MOULAY ABDELAZIZ ABOULHASSAN (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
In this work, the treatment of synthetic textile wastewater using sequential batch reactor (SBR) was studied. This in order to predict the effectiveness of biological treatment on wastewater containing dyes while minimizing the aeration cost. Laboratory tests were performed on synthetic wastewater containing filtered urban wastewater (source of bacteria) and dyes solutions. This promotes the biomass development in the mixture, capable of degrading organic matter properly. The results indicate that the increasing of anaerobic phase (16 hours) allows removal of 77 % and 80 % of COD and colour, respectively. The sludge age did not affect markedly dyes biodegradability. However, the biodegradability is strongly influenced by the dyes concentration. Indeed, for the lowest dyes contents, improved biodegradability was observed, while it decreases when the dyes concentration increases.